Psychometric Properties of the Turkish Version of the Substance Abuse Self-Stigma Scale - Sukut, Özge; Buzlu, Sevim (Addicta: The Turkish Journal on Addictions, 2022)
The aim of the study was to evaluate the psychometric properties of the Turkish version of the Substance Abuse Self-Stigma Scale-TR. The data were collected from 260 participants with substance use disorder history who were attending group therapy in the Istanbul Probation Department between April 4 and May 1, 2016. Using exploratory factor analyses, internal consistency, split-half reliability, construct validity, and concurrent validity were evaluated. The Cronbach’s alpha reliability coefficient of the Substance Abuse Self-Stigma Scale-TR was .77. Item-total correlation coefficients for the scale items were between .30 and .63. According to confirmatory factor analysis, chi-square/degrees of freedom ratio was 1.69 and rootmean-square error of approximation was .05 (p < .01). There was a strong positive correlation between the Substance Abuse Self-Stigma Scale-TR and the Internalized Stigma of Mental Illness Scale (r = .712; p < .001). These preliminary findings should be confirmed in larger-scale, multi-center studies among patients in long-term treatment. This study indicates that the Substance Abuse Self-Stigma Scale-TR is a reliable and valid instrument for determining self-stigma in individuals with substance use disorder.